Knowledge, attitude and practice (KAP) towards sleep among medical students Of International Islamic University Malaysia (IIUM) - Al-Naggar, Redhwan Ahmed; Musa, Ramli; Al-Jashamy, Karim; Md Isa, Zaleha (ASEAN Federation of Psychiatry, 2010)
Objective: To determine the knowledge, attitude and practice (KAP) of sleep among medical students of IIUM towards and to determine the impact of socio-demographic data on the knowledge, attitude and practice. Methods: A cross-sectional study was carried out among 106 students from first, second and third year medical students of IIUM. Verbal consent was taken from the students who were willing to take part in this study. Student knowledge about sleep was studied using a questionnaire. Results: A total of 106 medical students completed the survey, there were 54 female and 52 male. The mean age of the students was 20 ± 0.56 and ranged from 18 to 22 years. In terms of their sleep knowledge, the mean ± SD knowledge, attitude and practice scores were 81.8 ± 16.8, 65.9 ±15.3 and 176 ± 26.3 respectively. In univariate analysis, there was a significant difference between parents’ marital status regarding knowledge of the students (p = 0.03). There was a significant difference between gender regarding attitude of the students (p=0.05). In multivariate analysis, gender and smoking status were significantly affected the overall KAP. Conclusion: This study showed that sleep medicine knowledge was generally low among medical students. Therefore, educational strategies to improve knowledge regarding sleep-related problems and the development of proper sleep practices among medical students are needed.